Dengue hemorrhagic fever as a rare cause of chronic immune thrombocytopenic purpura—a pediatric case report - V. Thadchanamoorthy; Kavinda Dayasiri (Tropical Medicine and Health, 2020)
Abstract Background Dengue is a common mosquito-borne infection in tropical countries. Dengue incidence in Sri Lanka is generally showing a rising trend. Both chronic immune thrombocytopenia purpura (ITP) children and chronic ITP triggered by dengue fever in the pediatric age group are rarely reported. This unusual presentation is a diagnostic challenge to clinicians. The authors have reported a pediatric patient who presented with chronic ITP following recovery from dengue hemorrhagic fever. Case presentation A 14-year-old previously healthy boy was initially managed as for dengue hemorrhagic fever. Following initial detection of persistent thrombocytopenia at 2 weeks post-discharge, his parents defaulted follow-up for 1 year as he remained asymptomatic. However, 1 year after initial admission, the child re-presented with ecchymotic patches and a platelet count of 30 × 103/cumm. Review of serial blood counts performed during previous hospital admission and by his parents themselves revealed persistent thrombocytopenia over preceding 12 months. Subsequently, the child had an in-depth evaluation. The diagnosis of ITP was confirmed by ruling out differential diagnosis and he was managed as for chronic ITP. His platelet counts showed good response to oral corticosteroids and he is currently being followed up at the pediatric hematology clinic. Conclusion While reporting, a 14-year-old boy who developed chronic ITP following dengue hemorrhagic fever, this report highlights importance of frequent monitoring of blood counts to accurately detect and manage critical phase of dengue fever. The report also highlights the value of monitoring platelet counts in post-recovery phase to ensure they have normalized.